2011
DOI: 10.1186/1475-2859-10-s1-s20
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages of lactic acid bacteria and their impact on milk fermentations

Abstract: Every biotechnology process that relies on the use of bacteria to make a product or to overproduce a molecule may, at some time, struggle with the presence of virulent phages. For example, phages are the primary cause of fermentation failure in the milk transformation industry. This review focuses on the recent scientific advances in the field of lactic acid bacteria phage research. Three specific topics, namely, the sources of contamination, the detection methods and the control procedures will be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
158
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(163 citation statements)
references
References 101 publications
(113 reference statements)
1
158
0
4
Order By: Relevance
“…Thin sections revealed that TP712 virions appeared to be correctly assembled inside the DftsH host, but were not released. These virions were infective, demonstrating that a functional host FtsH is required by TP712 to proceed effectively with lysis of the host.Large-scale dairy fermentations can be seriously compromised by bacteriophages infecting lactic acid bacteria (LAB), and particularly Lactococcus lactis, which is a commonly used starter culture for cheese making (Garneau & Moineau, 2011). Lactococcal phages are currently classified in 10 groups, eight of them belonging to the Siphoviridae family of the order Caudovirales.…”
mentioning
confidence: 99%
“…Thin sections revealed that TP712 virions appeared to be correctly assembled inside the DftsH host, but were not released. These virions were infective, demonstrating that a functional host FtsH is required by TP712 to proceed effectively with lysis of the host.Large-scale dairy fermentations can be seriously compromised by bacteriophages infecting lactic acid bacteria (LAB), and particularly Lactococcus lactis, which is a commonly used starter culture for cheese making (Garneau & Moineau, 2011). Lactococcal phages are currently classified in 10 groups, eight of them belonging to the Siphoviridae family of the order Caudovirales.…”
mentioning
confidence: 99%
“…The polymerase chain reaction (PCR), ELISA and flow cytometry-based methods have been designed for detecting phages and are often used to complement microbiology tests. However, they have still many drawbacks to be applied for routine analyses in the dairy industry [104].…”
Section: Sensitive Methods (Including Elisa and Molecular Dna Techniqmentioning
confidence: 99%
“…Running on the flow-cytometry of samples containing phages gives a broad distribution of cell mass (wide peak), which demonstrates the presence of both lysed and live cells, while non-infected samples give narrow peaks. Flow-cytometry allows detection of phages in real time, but expensive equipment and well-trained staff needed to perform the assays limits application of this technique in the dairy industry [104].…”
Section: Sensitive Methods (Including Elisa and Molecular Dna Techniqmentioning
confidence: 99%
“…Another aspect to take in consideration is the undesirable implication in cheese making when specific lactic phages infect and lyse LAB (lactic acid bacteria) which are indispensable for milk curdling [21,22].…”
Section: Introductionmentioning
confidence: 99%